2021
DOI: 10.3390/sports10010002
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Kinematic Characteristics of Proficient and Non-Proficient 2-Point and 3-Point Basketball Shooters

Abstract: The purpose of this study was to examine kinetic and kinematic characteristics of various types of 2-point and 3-point basketball shooting approaches and determine which variables have the greatest contribution in discriminating proficient (PRO) from non-proficient (N-PRO) shooters. While standing on a force plate, twenty-nine recreationally active males performed a total of 1740 shots by utilizing stationary and step-in shooting approaches. Two high-definition cameras were used to simultaneously capture kinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 18 publications
6
24
2
Order By: Relevance
“…Cabarkapa et al [15] recently found that proficient shooters had higher elbow positioning when compared to non-proficient shooters during two-point shooting motions, which is similar to the findings of the present study. When entered into a full discriminant function model, elbow height showed as the key variable capable of classifying proficient from non-proficient two-point shooters; it accounted for approximately 52% of the total explained variance [15].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Cabarkapa et al [15] recently found that proficient shooters had higher elbow positioning when compared to non-proficient shooters during two-point shooting motions, which is similar to the findings of the present study. When entered into a full discriminant function model, elbow height showed as the key variable capable of classifying proficient from non-proficient two-point shooters; it accounted for approximately 52% of the total explained variance [15].…”
Section: Discussionsupporting
confidence: 92%
“…Cabarkapa et al [15] recently found that proficient shooters had higher elbow positioning when compared to non-proficient shooters during two-point shooting motions, which is similar to the findings of the present study. When entered into a full discriminant function model, elbow height showed as the key variable capable of classifying proficient from non-proficient two-point shooters; it accounted for approximately 52% of the total explained variance [15]. Besides higher elbow positioning, previous research has indicated that positioning the elbow under the ball in line with the basket (i.e., shooting plane of motion) can elicit further improvements in shooting accuracy [4,7].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations